Indigenous Bodies, Maya Minds : Religion and Modernity in a Transnational K'iche' Community - MacKenzie, C. James (Book collections on Project MUSE., 2016)
""MacKenzie examines tension and conflict over ethnic and religious identity in the K'iche' Maya community of San Andres Xecul in the Guatemalan highlands, and considers how religious and ethnic attachments are sustained and transformed through the transnational experiences of locals who have migrated to the United States"--Provided by publisher"--